1997
DOI: 10.1007/s11357-997-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and oxidative stress: Sources of free radicals and their impact on antioxidant systems

Abstract: Strenuous exercise is characterized by increased oxygen consumption and the disturbance between intracellular pro-oxidant and antioxidant homeostasis. At lease three biochemical pathways (i.e., mitochondrial electron transport chain, xanthine oxidase, and polymorphoneutrophil) have been identified as potential sources of intracellular free radical generation during exercise. These deleterious reactive oxygen species pose a serious threat to the cellular antioxidant defense system, such as diminished reserves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0
10

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 121 publications
(207 reference statements)
2
52
0
10
Order By: Relevance
“…Some production of RONS is necessary for normal contractile activity of skeletal muscles [72,144], and physical training is a known to induce antioxidant enzymes [44,61]. However, strenuous exercise, mainly if above habitual intensity of effort, or training with very elevated frequency, generally overloads the endogenous antioxidant system's capacity, leading to an increase in plasma lipid peroxidation [44] plus oxidative damage to muscles and other tissues [44,61,128,132].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some production of RONS is necessary for normal contractile activity of skeletal muscles [72,144], and physical training is a known to induce antioxidant enzymes [44,61]. However, strenuous exercise, mainly if above habitual intensity of effort, or training with very elevated frequency, generally overloads the endogenous antioxidant system's capacity, leading to an increase in plasma lipid peroxidation [44] plus oxidative damage to muscles and other tissues [44,61,128,132].…”
Section: Introductionmentioning
confidence: 99%
“…Some production of RONS is necessary for normal contractile activity of skeletal muscles [72,144], and physical training is a known to induce antioxidant enzymes [44,61]. However, strenuous exercise, mainly if above habitual intensity of effort, or training with very elevated frequency, generally overloads the endogenous antioxidant system's capacity, leading to an increase in plasma lipid peroxidation [44] plus oxidative damage to muscles and other tissues [44,61,128,132]. These damaging effects, with their consequent inflammatory processes, can jeopardize performance and may lead to overtraining syndrome, besides potentially contributing to an increased future risk of cardiovascular disease (CVD) [37,44,109,131,136].…”
Section: Introductionmentioning
confidence: 99%
“…Recommending antioxidant supplements should thus only be for cases when exhaustive exercise causes oxidative stress and cell damage. [9][10][11] Additionally, many potentially significant genetic variants related to oxidative stress have already been identified. [12,13] Among them, several single nucleotide polymorphisms (SNPs) in the antioxidant enzyme genes and null polymorphisms in glutathione S-transferases (GSTs) genes have been reported to produce altered or absent levels or activities of those enzymes, leading to lowered protection against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ability of the serum glycoprotein haptoglobin (Hp) to block hemoglobininduced oxidative stress and damage is reportedly phenotype dependent. [18] Since the prudent recommendation for physically active individuals is a diet rich in antioxidants from natural foods, [10] natural antioxidant supplementation can prevent exercise-induced damage in athletes who exercise strenuously and exceed their endogenous antioxidant defenses [9] or even for those who were born less genetically favored by the antioxidant defense system. In previous studies, our group demonstrated that carotenoid-rich oil from pequi (Caryocar brasiliense Camb.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the elevated reactive oxygen species (ROS) and urate generation during physical activity, [9][10][14][15][16] urate recirculation in the PT cells seems quite logical and may have some physiological importance in preventing hazardous effects of ROS and maintaining the integrity of the PT cells. Therefore, reduced urate reabsorption or excretion may deteriorate the maintenance of the normal uric acid homeostasis in exercisers.…”
Section: Introductionmentioning
confidence: 99%